Urban Space and Transportation in Hong Kong: A Travelogue - Ahmadin, Ahmadin (CV. ULIL ALBAB CORP, 2024)
Visiting Hong Kong for foreign tourists is a very pleasant thing, at least because not everyone has the opportunity to visit. On the other hand, Hong Kong has the attraction of being the most vertical city in the world with its skyscrapers and reclaimed urban spaces. This paper discusses the portrait of urban spaces and transportation in Hong Kong with the approach of Sociology of Space and Sociology of History. Data collection techniques are done through direct observation in Hong Kong and Kowloon, literature study, and interviews with tour guides. The results showed that Hong Kong as a former British colony, until now still holds a variety of European social and cultural heritage, including public spaces and transportation facilities. Some streets in Hong Kong as well as types of transportation facilities are still a British heritage that is still maintained